A brief reflection on absenteeism due to temporary incapacity and the role that collective agreements can play in its management - García Viña, Jordi (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
Absenteeism has become one of the major challenges in labor relations since the pandemic. While not a new issue, there have been both quantitative changes –the number of cases is increasing each year, along with a rise in total costs– and qualitative changes, as factors such as age and mental health, which have yet to be fully analyzed, have emerged, highlighting the need for solutions. While regulatory changes are necessary, particularly regarding the management of temporary disability, collective bargaining can be a strategic tool.
Keywords: Absenteeism; temporary disability; collective bargaining